2004
DOI: 10.1007/bf03325836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on chlorophyll concentration, leaf area, yield and yield components of rice genotypes grown under saline environment

Abstract: Salt tolerance in eighteen advanced rice genotypes was studied under an artificially salinized (EC=8.5 dSm-1) soil conditions after 90 days of transplanting. The results showed that the yield per plant, chlorophyll concentrations, fertility percentage, and number of productive tillers, panicle length and number of primary braches per panicle of all the genotypes were reduced by salinity. However, genotypes viz. Jhona-349 x Basmati-370, NR-1, DM-59418, DM-63275, DM-64198 and DM-38-88 showed better salinity tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
90
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 2 publications
19
90
1
3
Order By: Relevance
“…Islam et al (2011) on hybrid rice also reported that grain yields decreased by the salinity. Ali et al (2004) also found the similar result on grain yield of rice. Devar et al, 2013 found that grain yield and stover yield significantly decrease under salt stress and proline application helps to ameliorate the salinity problem.…”
Section: Grain and Stover Yieldssupporting
confidence: 67%
“…Islam et al (2011) on hybrid rice also reported that grain yields decreased by the salinity. Ali et al (2004) also found the similar result on grain yield of rice. Devar et al, 2013 found that grain yield and stover yield significantly decrease under salt stress and proline application helps to ameliorate the salinity problem.…”
Section: Grain and Stover Yieldssupporting
confidence: 67%
“…Salt tolerance in the Triticeae is associated with enhanced ability to discriminate between Na + and K + in the soil solution and to preferentially accumulate K + and exclude Na + (Omielan, et aI., 1991 andAli, et al, 2004). In the present study, almost all the wheat genotypes responded varyingly to external potassium application.…”
Section: Discussionmentioning
confidence: 52%
“…Proline application did not remarkably affect chlorophyll contents in BARI Hybrid Maize-5 induced by salt stress although increased chlorophyll contents in Hybrid Maize Pacific-987 were observed by proline under salt stress (Table 2). Reduction in chlorophyll content has been reported in plants in response to salt stress (Ali et al, 2004;Islam et al, 2007;Sobahan et al, 2012;Talat et al, 2013). Conversely, exogenous application of proline increased chlorophyll content in a variety of plants reported by several authors (Deivanai et al, 2011;Sobahan et al, 2012;Talat et al, 2013).…”
Section: K + /Namentioning
confidence: 95%